Pengaruh Model Pembelajaran Kooperatif Tipe Double Loop Problem Solving terhadap Kemampuan Penalaran Adaptif dan Disposisi Matematis pada Materi Trigonometri - Khoirunnisa, Risma Arum; Rahma, Nadya Alvi (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2023)
This study was motivated by the low quality of education in Indonesia based on the results of PISA 2018, the implementation of the 2013 Curriculum which did not follow the use of appropriate learning models, as well as the low adaptive mathematical reasoning abilities and mathematical disposition of students. This research aims to determine the influence of the Double Loop Problem-Solving cooperative learning model on the adaptive reasoning abilities and mathematical disposition of class X students at SMA Negeri 1 Karangan on Trigonometry material. This research was conducted using a quantitative approach with a Quasi-Experimental research type and a Nonequivalent Posttest-Only Control Group Design. As for sampling, non-probability sampling was used with the Purposive Sampling technique with class X MIPA 3, totaling 35 students, as the experimental class and X MIPA 4, totaling 36 students, as the control class. Data collection techniques using tests, questionnaires, and documentation. The data analysis technique in this research uses the Manova test. The research results show that there is a significant influence due to the application of the Double Loop problem-solving cooperative learning model on students' adaptive reasoning abilities and mathematical disposition.